The Role of Sinden in Wayang Golek: Functions And Challenges - Krismayanty, Mayang; Wastap, Jaeni B; Saleh, Sukmawati (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
In this era, the artists who preserve wayang golek are elderly. The urge need of the next generation to continue the journey of this art. Especially a sinden, in this art the role of sinden is very important even almost equivalent to the dalang. There are many young people who already have artist legality, whether academically or not. But rarely are they willing and able to be involved in the realm of wayang golek. This obstacle is related to the very high musical complexity. The focus of this research is to analyze the role of a sinden in wayang golek performances, both in terms of functions and challenges. The method in this research uses descriptive qualitative, with data collection techniques through literature and field study. Literature study is in the form of theses and dissertations. This technique to analyze previous studies related to the object of research. Field study techniques, namely data collection by means of observation, interviews, document collection, and triangulation. The position of sinden in this performance is very important, visual aesthetics and musicality of sinden are very influential on the success of a wayang performance. This is a big challenge for anyone who wants to become a wayang singer. Understanding Sundanese musical knowledge and lakon wayang is the main asset for a sinden. Also the risk of social pressure by facing society’s negative paradigm towards the profession of sinden. This study explored more deeply the specific functions and challenges of sinden wayang golek, visually, musically and socially.